Optimal structure determination from sub‐optimal diffraction data. (24th November 2021) - Minor, Wladek; Cymborowski, Marcin; Borek, Dominika; Cooper, David R.; Chruszcz, Maksymilian; Otwinowski, Zbyszek
Abstract: Herein we present the newest version of the HKL‐3000 system that integrates data collection, data reduction, phasing, model building, refinement, and validation. The system significantly accelerates the process of structure determination and has proven its high value for the determination of very high‐quality structures. The heuristic for choosing the best approach for every step of structure determination for various quality samples and diffraction data has been optimized. The latest modifications increase the likelihood of a successful structure determination with challenging data. The HKL‐3000 is a successor of HKL and HKL‐2000 programs. The use of the HKL family of programs has been reported for over 73, 000 PDB deposits, that is, almost 50% of macromolecular structures determined with X‐ray diffraction.